Bidirectional associations between maladaptive cognitions and emotional symptoms, and their mediating role on the quality of life in adults with ADHD: a mediation model - Pan, Mei-Rong; Zhang, Shi-Yu; Chen, Cai-Li; Qiu, Sun-Wei; Liu, Lu; Li, Hai-Mei; Zhao, Meng-Jie; Dong, Min; Si, Fei-Fei; Wang, Yu-Feng; Qian, Qiu-Jin (Frontiers in Psychiatry, 2023)
Background/Objectives: Adults with attention-deficit/hyperactivity disorder (ADHD) have more maladaptive cognitions, emotional problems and a poorer quality of life (QoL). A verification of the psychological model in clinical samples is needed for a better understanding of the mechanisms of ADHD diagnosis on QoL via maladaptive cognitions, emotional symptoms, and their interactions. Methods: 299 ADHD participants and 122 healthy controls were recruited. ADHD core symptoms, maladaptive cognitions, emotional symptoms and psychological QoL were rated. Pearson's correlation and structural equation modeling were analyzed to explore the relationship and influence of ADHD diagnosis on QoL. Results: More maladaptive cognitions, emotional symptoms, and poorer QoL were found in the ADHD group, and the dysfunctional attitudes were on par between ADHD with or without medication (p = 0.368). Moderate to strong correlations were found between emotional symptoms, maladaptive cognitions and QoL, and ADHD core symptoms presented correlations among the above scores (r = 0.157 ~0.416, p < 0.01) in ADHD participants. The influence of ADHD diagnosis on QoL was mediated through maladaptive cognitions, emotional symptoms, and their bidirectional interactions (p < 0.05), especially those with stable medication. Conclusions: Our study is the first to verify the psychological model in adults with ADHD in China. The findings determined the direct influence of ADHD diagnosis on QoL and the indirect influence through maladaptive cognitions, emotional symptoms, and their interactions, emphasizing the importance of interventions for emotional symptoms and maladaptive cognitions for ADHD patients both with or without medication for a better QoL outcome.